Rancang Bangun Sistem Informasi Manajemen Arsip Kerja Sama Pada PT. Kelola Teknologi Informasi - Dody Firmansyah; Siti Ernawati (BIOS : Jurnal Teknologi Informasi dan Rekayasa Komputer, 2023)
Currently, in the globalization era, sophisticated technology, and one of them is a website-based information system used as information management tools using the internet. Hence by using web-based information system, not only simplifies and speeds up the work but also saves time and cost. The one example of the problem that the authors take is the design of the cooperation archive management information system at PT. Kelola Teknologi Informasi which is still manual, that the company staff organizes archives and documentation in computer folders and recapitulates in the number processing application (Excel). This study was conducted to build a website-based archive management information system. The system development Model used is Waterfall. The tests carried out are website performance and security tests. Performance testing results show that the website performs the desired functions with fast response times. While the results of website security testing using Quttera found that there was no malicious content detected and declared clean. With this information system makes it easier for archive and documentation systems to be accessed online by anyone and anywhere who has access.